2016
DOI: 10.1364/oe.24.020365
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Bragg filters with a phase transition material defect layer

Abstract: Abstract:We propose an all-solid-state tunable Bragg filter with a phase transition material as the defect layer. Bragg filters based on a vanadium dioxide defect layer sandwiched between silicon dioxide/titanium dioxide Bragg gratings are experimentally demonstrated. Temperature dependent reflection spectroscopy shows the dynamic tunability and hysteresis properties of the Bragg filter. Temperature dependent Raman spectroscopy reveals the connection between the tunability and the phase transition of the vanad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…For example, tunable near-IR Bragg filters have been demonstrated by introducing thinfilm VO 2 as a defect layer into an alternating TiO 2 /SiO 2 optical stack by depositing all the layers on a bulk quartz substrate using conventional magnetron sputtering. 41 However, for the LWIR regime, very few transparent materials are convenient substrates for growth of VO 2 42,43 . Here, we demonstrated that a VO 2 film can be introduced into mid-IR-transparent stacks by first synthesizing VO 2 on a thin Si membrane and then depositing additional thin films on both sides.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tunable near-IR Bragg filters have been demonstrated by introducing thinfilm VO 2 as a defect layer into an alternating TiO 2 /SiO 2 optical stack by depositing all the layers on a bulk quartz substrate using conventional magnetron sputtering. 41 However, for the LWIR regime, very few transparent materials are convenient substrates for growth of VO 2 42,43 . Here, we demonstrated that a VO 2 film can be introduced into mid-IR-transparent stacks by first synthesizing VO 2 on a thin Si membrane and then depositing additional thin films on both sides.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the filters are much desired for multiplicity applications, specifically in periodic waveguides structure [2]. The introduction of defects into the periodic structure generates localized narrow bands, which can be utilized for the construction of filters with an exceptionally narrow transmission band [3]. In most studies, filters are focused on the photonic band gaps (PBGs) manipulation, i.e., all defects modes are designed to set within PBGs.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of VO 2 increases by several orders of magnitude during the transition. Up to now, research on VO 2 -based devices has involved many aspects, such as optical switch [18]- [20], absorber [21]- [23], and filter [24]- [26]. In 2018, M. Sun et al proposed a photonic switch based on VO 2 material, whose structure is composed of an array of hexagonal nanoholes [27].…”
mentioning
confidence: 99%